1997
DOI: 10.1086/516171
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline Therapy for Chronic Lyme Disease

Abstract: Two hundred seventy-seven patients with chronic Lyme disease were treated with tetracycline for 1 to 11 months (mean, 4 months); the outcomes for these patients were generally good. Overall, 20% of the patients were cured; 70% of the patients' conditions improved, and treatment failed for 10% of the patients. Improvement frequently did not take place for several weeks; after 2 months of treatment, 33% of the patients' conditions were significantly improved (degree of improvement, 75%-100%), and after 3 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
91
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 20 publications
4
91
0
2
Order By: Relevance
“…Three of these randomized trials have been criticized as offering "too little, too late" [68][69][70], based on retrospective, open-label case-series that suggested a possible role of prolonged antibiotic therapy in patients diagnosed with "chronic Lyme disease" [71,72]. In general, caseseries studies are fraught with potential for biases.…”
Section: Studies Of Antibiotic Treatment In Post-lyme Disease Syndromementioning
confidence: 99%
“…Three of these randomized trials have been criticized as offering "too little, too late" [68][69][70], based on retrospective, open-label case-series that suggested a possible role of prolonged antibiotic therapy in patients diagnosed with "chronic Lyme disease" [71,72]. In general, caseseries studies are fraught with potential for biases.…”
Section: Studies Of Antibiotic Treatment In Post-lyme Disease Syndromementioning
confidence: 99%
“…For example, 10 days versus 30 days (Stanek & Strle, 2003) doxycyclin treatment were also suggested. Moreover we found a study applying 11 months long treatment (Donta, 1997). In contrast, azithromycin described to be effective in a five day course (Arnez et al, 2002, Hunfeld et al, 2005.…”
Section: Introductionmentioning
confidence: 88%
“…[34][35][36] These limitations include using loose case definitions for post-Lyme disease syndrome and interpretation of Lyme disease diagnostic testing criteria that is not consistent with the current recommendations by the Centers for Disease Control and Prevention. In addition, controlled trials found that up to 40% of subjects with post-Lyme disease syndrome report a positive response to placebo.…”
Section: Treatment Of Lyme Diseasementioning
confidence: 99%